Diversifikasi Pangan Olahan Jagung Manis Untuk Meningkatkan Pendapatan LMDH Wanasari Di Sekitar Hutan - Fitri Yulinar Aldila; Gevyma Tharis Iftikhor; Muhammad Khawarizmi; Taufik Setyadi (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
Efforts to diversify corn-based processed products have not been widely carried out by the community, including LMDH in Candisari village, Lamongan Regency. This is due to the lack of knowledge and skills in the community regarding innovations in corn-based food processing, and people are more likely to sell corn directly to middlemen to make ends meet. The main aim of this socialization is to provide LMDH with a solution on how to use sweet corn in the Candisari Village area to process it into marketable food products using simple technology. This is the basis for socialization activities and the use of corn processing carried out in Candisari Village, Sambeng District, Lamongan Regency. The result of the socialization is an increase in community knowledge and skills in innovation in corn pudding processing and product marketing.